Non-extensive statistics in spin precession. (9th January 2017) - Bales, M. J.; Fierlinger, P.; Golub, R.
Abstract: Many experiments utilize the precession of trapped particles in magnetic fields to perform high-precision measurements. It has often been presumed that after free precession, initially polarized particles will form a Gaussian phase distribution in the plane of precession. We show that trapped particles in the presence of magnetic-field gradients and electric fields will often form a non-Gaussian distribution with power-law tails with the exact shape of the distribution depending upon many experimental parameters. The results are consistent with distributions predicted by non-extensive statistics.